2016
DOI: 10.1016/j.diagmicrobio.2016.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Neisseria gonorrhoeae from 4 commercially available transport systems

Abstract: Four commercial transport systems for the recovery of Neisseria gonorrhoeae were evaluated in support of the need to obtain culture isolates for the detection of antimicrobial resistance. Bacterial recovery from the InTray GC system was superior with minimal loss of viability in contrast to non-nutritive transport systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…These data support a previous study examining four commercial transport systems and comparing recovery rates between the systems, which found that the InTray GC had optimal recovery of specimen in comparison to other systems [7]. Our study builds upon this research by demonstrating that the InTray GC plates could be subjected to extended transport times up to 72 hours without significant loss of specimen viability.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…These data support a previous study examining four commercial transport systems and comparing recovery rates between the systems, which found that the InTray GC had optimal recovery of specimen in comparison to other systems [7]. Our study builds upon this research by demonstrating that the InTray GC plates could be subjected to extended transport times up to 72 hours without significant loss of specimen viability.…”
Section: Discussionsupporting
confidence: 85%
“…The strain growth in terms of percent recovery for four of the strains on the InTray GC (AR 0181, AR 0197, AR0202, AR0175) could also potentially be confounded by the initial bacterial load in each sample. However, based on prior studies examining recovery on the InTray GC, we did not expect to see vast declines between time points, and rather expected to see small log 10 increases and decreases [7]. This research is integral to future research and monitoring of antibiotic resistance in N. gonorrhoeae.…”
Section: Plos Onementioning
confidence: 88%
See 2 more Smart Citations
“…Different culture media used and variable techniques in either culture collection by different clinicians or transport of cultures from clinics to testing laboratories might also affect NG isolation rates. 11 All 3 jurisdictions used the same driving principle to define their culture criteria (i.e., likelihood of positivity). However, some patients from whom specimens for culture were collected during SURRG but who did not meet the criteria examined in the pre-SURRG data period might explain some unexpected findings in the SURRG-period analyses.…”
Section: Discussionmentioning
confidence: 99%